Impacts of Growing Number of Taxable Entrepreneurs on the Revenue of Value Added Tax - Febriansyah, A; Aprilia, R T; Gunawan, S (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to determine how much impact of the Number of Taxable Entrepreneurs on Value Added Tax (VAT) Revenue at the Madya Bandung Tax Service Office. The research method used is descriptive and verification methods with a quantitative approach. The sampling technique used is the Non-Probability Sampling technique with the determination of sampling using Saturated Sampling.The data analysis method used in this study is multiple linear regression analysis using SPSS v25 software.The results of this study indicate that partially the Number of Taxable Entrepreneurs has an positive impact on the of Value Added Tax Revenue at the Bandung Madya Tax Service Office. which means that the increasing number of taxable entrepreneurs will have an impact on increasing value added tax revenues at the Bandung Madya Tax Service Office